Cost Analysis of Nursing Activities for COVID-19 Patients in the Accident and Emergency Room of a Secondary Hospital - Compesh, Wilairat; Singchungchai, Phechnoy; Chatdokmaiprai, Kannikar (NU Journal of Nursing and Health Sciences, 2022)
The objective of this descriptive research was to analyze the cost of nursing activities for COVID-19 patients in the accident and emergency room of a secondary hospital. From the perspective of the health care provider. The target population was 26 personnel cost reports of all the nursing personnel. The subject group was 30 COVID-19 patient cost reports selected using purposive sampling. Three research instruments used were 1) a dictionary of nursing activities consisting of 4 main activities, 2) records of nursing activities and time of the activities, and 3) records of cost per unit of service. The content validity index (CVI) of the research instruments was 00.92 and the observation validity was 0.88. The data were analyzed with descriptive statistics of frequency, percentage, mean, and standard deviation. The research found that the total cost of nursing activities was 1,310,118.94 Baht with the highest cost of nursing care activities during treatment at 476,763.48 Baht (36.39 percent). When analyzing the cost per activity, it was found that the highest cost per activity was nursing care activities during treatment at 4,276.65 Baht. The cost per case was 43,670.64 Baht. It was also found that the materials with high costs were personal protective equipment (PPE), and severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) using real-time-polymerase chain reaction (RT-PCR) tests which require approximately one-day wait-time for the result, and labor cost in the cost of risk. This research on the cost analysis of nursing activities in the accident and emergency room considered is new and important for nursing administrators. Thus, the data should be utilized in the management of budget, resources, and time to increase work efficiency in dealing with emerging infectious diseases in the future.